A new typology for the logic of appropriateness in Fiji. Issue 2 (1st October 2013) - Ramesh, Sanjay
This article utilizes public choice theory, in particular the logic of appropriateness analysis, developed by James March, on recognition, identity and rules to argue that political appropriateness in Fiji was centred around communal considerations. As such, it was incompatible with multiracial governance, which resulted in conflict between Indo-Fijians and indigenous Fijians which in turn caused internal factionalization within indigenous Fijians, leading to coups and civil unrest in 2000 and 2006. However, since the December 2006 coup, there have been attempts by the military-led regime to change the communal logic towards a new logic based on ethnic inclusiveness, which allowed for the framing of a new political typology where all ethnic groups in Fiji have equal citizenry. However, the article identifies that there may be risks involved with the new political structuration process where contending rules and identities of the past may not be reconciled, creating a circulatory that undermines the new logic trajectory. Regional governments, Australia and New Zealand, imposed travel bans on Fiji government ministers and a number of local Non Government Organizations and unions have criticized the military led regime of being autocratic and insensitive to the concerns of indigenous Fijians. Nevertheless, the article suggests that there is an opportunity for cementing the new logic by setting up deliberative forms of governance including reforms to parliamentary institutions through a committee system where conflicting views and ideas can be debated and reconciled.